Complement, C1q, and C1q-Related Molecules Regulate Macrophage Polarization - Bohlson, Suzanne S.; O’Conner, Sean D.; Hulsebus, Holly Jo; Ho, Minh-Minh; Fraser, Deborah A. (Frontiers in Immunology, 2014)
Complement is a critical system of enzymes, regulatory proteins and receptors that regulates both innate and adaptive immune responses. Natural mutations in complement molecules highlight their requirement in regulation of a variety of human conditions including infectious disease and autoimmunity. As sentinels of the immune system, macrophages are specialized to respond to infectious microbes, as well as normal and altered self, and dictate appropriate immune responses. Complement components such as anaphylatoxins (C3a and C5a) and opsonins (C3b, C1q, MBL) influence macrophage responses. While anaphylatoxins C3a and C5a trigger inflammasome activation, opsonins such as C1q and related molecules (MBL and adiponectin) downregulate inflammasome activation and inflammation, and upregulate engulfment of apoptotic cells consistent with a pro-resolving or M2 macrophage phenotype. This review summarizes our current understanding of the influence of the complement system on macrophage polarization with an emphasis on C1q and related molecules.